Muscle coactivation before and after the impact phase of running following isokinetic fatigue - Kellis, E.; Zafeiridis, A.; Amiridis, I. G. (Journal of Athletic Training, 2011)
Context: The effects of fatigue on impact loading during running are unclear, with some authors reporting increased impact forces and others reporting decreased forces.